Function of Treg Cells Decreased in Patients With Systemic Lupus Erythematosus Due To the Effect of Prolactin. Issue 5 (February 2016) - Legorreta-Haquet, María Victoria; Chávez-Rueda, Karina; Chávez-Sánchez, Luis; Cervera-Castillo, Hernando; Zenteno-Galindo, Edgar; Barile-Fabris, Leonor; Burgos-Vargas, Rubén; Álvarez-Hernández, Everardo; Blanco-Favela, Francisco
Abstract : Abstract: Prolactin has different functions, including cytokine secretion and inhibition of the suppressor effect of regulatory T (Treg ) cells in healthy individuals. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by defects in the functions of B, T, and Treg cells. Prolactin plays an important role in the physiopathology of SLE. Our objective was to establish the participation of prolactin in the regulation of the immune response mediated by Treg cells from patients with SLE. CD4 + CD25 hi CD127 −/low cells were purified using magnetic beads and the relative expression of prolactin receptor was measured. The functional activity was evaluated by proliferation assay and cytokine secretion in activated cells, in the presence and absence of prolactin. We found that both percentage and function of Treg cells decrease in SLE patients compared to healthy individuals with statistical significance. The prolactin receptor is constitutively expressed on Treg and effector T (Teff ) cells in SLE patients, and this expression is higher than in healthy individuals. The expression of this receptor differs in inactive and active patients: in the former, the expression is higher in Treg cells than in Teff cells, similar to healthy individuals, whereas there is no difference in the expression between Treg and Teff cells from active patients. In Treg :Teff cell cocultures, addition of prolactin decreases the suppressor effect exerted by Treg cells and increases IFNγ secretion. Our results suggest that prolactin plays an important role in the activation of the disease in inactive patients by decreasing the suppressor function exerted by Treg cells over Teff cells, thereby favoring an inflammatory microenvironment. Abstract : Supplemental Digital Content is available in the text